Development of Import-Based Exports in Turkey: The ARDL Approach - Yaşar Turna (Istanbul Business Research)
Turkey adopted an export-dependent growth strategy after the 1980 liberalization. In later years, with the impact of this strategy, Turkey's export structure and performance became a subject of investigation. Thus, when the export structure is evaluated, dependence of the export oriented industries on capital goods, intermediate goods, and energy is remarkable. Therefore, in this study, the development of import-based exports in Turkey between 1996:1 and 2018:4 was tested by the ARDL bound test method. As a result of the analyses, the effect of intermediate goods, capital goods, and energy imports, which have a higher amount of imports than other imported goods in the short and long term in Turkey, is noteworthy. Hence, the study is important and different from other studies in that it verifies the Turkey’s industrial structure tending towards the assembly industry since its recent export structure has shown an import-oriented development and the share of imports of intermediate goods in its exports is high.